2021
DOI: 10.24815/siele.v8i3.20122
|View full text |Cite
|
Sign up to set email alerts
|

Discourse markers in academic and non-academic writings of Thai EFL learners

Abstract: The ability to use discourse markers (DMs) to create cohesion and coherence of a text is essential for EFL learners at the university level to express ideas and thoughts in various types of writing assignments, such as academic papers and reflections. Hence, this study attempted to shed more light on the use of DMs in academic and non-academic writings of Thai EFL learners. The main objective was to investigate the types, overall frequency, and differences, and similarities of discourse markers in both styles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Putting everything in a nutshell, with the incorrect discourse markers identified that shown some problematic usage from 62 electronic essays of First-year English Language Majors, it may be deduced that students are still unaware about the basic function of every discourse marker that resulted to incorrect and ungrammatical use of these words. This is supported on the conclusions of the previous studies that highlight the important acquisition of the knowledge on discourse markers by the students as it would improve the quality of their written outputs (Riznanda, 2021;Choemue and Bram, 2021;Ni'mah, 2019;Al-khazraji, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Putting everything in a nutshell, with the incorrect discourse markers identified that shown some problematic usage from 62 electronic essays of First-year English Language Majors, it may be deduced that students are still unaware about the basic function of every discourse marker that resulted to incorrect and ungrammatical use of these words. This is supported on the conclusions of the previous studies that highlight the important acquisition of the knowledge on discourse markers by the students as it would improve the quality of their written outputs (Riznanda, 2021;Choemue and Bram, 2021;Ni'mah, 2019;Al-khazraji, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, teachers should focus on different teaching methods in writing classes while teaching DMs in order to decrease the number of misused and overused DMs. Each DM can be taught separately with its function and place in the paragraph in writing classes (Choemue & Bram, 2021). Sun (2013) reaches a conclusion that DMs affect learning since learning consists of comprehension and production.…”
Section: Discussionmentioning
confidence: 99%
“…With it, the findings are elaborated as detail as possible and presented in form of paragraph to give the target readers, namely the novice writers, a clear picture on how to write research articles. The data of this present study is a research article written by Choemue & Bram (2021) entitled "Discourse Markers in Academic and Non-Academic Writings of Thai EFL Learners ". This research article is selected because it is published in 2021 by a journal indexed by Scopus Q1 and Sinta 1.…”
Section: Methodsmentioning
confidence: 99%
“…The research article is written by Choemue & Bram (2021) entitled "Discourse Markers in Academic and Non-Academic Writings of Thai EFL Learners ". It is published in 2021 by a journal indexed by Scopus Q1 and Sinta 1.…”
Section: Summary Of the Research Articlementioning
confidence: 99%